Spacecraft systems engineering - Fortescue, Peter; Fortescue, Peter W.; Stark, John.; Swinerd, Graham (Hoboken, N.J. : Wiley, 2011)
"Updated edition of this bestselling & well-established introductory guide to the engineering of spacecraftThoroughly revised and updated, this fourth edition of Spacecraft Systems Engineering provides the reader with comprehensive coverage of all the different areas of engineering required in the design and implementation of spacecraft and space missions. The authors describe the workings of various types of spacecraft systems together with the essential disciplines which ensure that they work reliably and in harmony with each other. With emphasis on recent developments in space activities, all chapters have been rewritten with major revisions to the chapters on launch vehicles, structures, ground stations and mechanisms, and a brand new chapter on Assembly, Integration and Test. Spacecraft Systems Engineering, 4th edition begins with front-end system level issues such as environment, mission analysis and system engineering, and progresses to a detailed examination of subsystem elements which represent the core of spacecraft design - mechanical, electrical, propulsion, thermal, control etc. This quantitative treatment is supplemented by an appreciation of the interactions between the elements, which deeply influence the process of spacecraft systems design"--
"Thoroughly revised and updated, this fourth edition of Spacecraft Systems Engineering, 4th edition provides the reader with comprehensive coverage of all the different areas of engineering required in the design and implementation of spacecraft and space missions"--
The spacecraft environment and it's effect on the design -- Dynamics of spacecraft -- Celestial mechanics -- Mission analaysis -- Propulsion systems -- Launch vehicles -- Spacecraft structures -- Attitude control -- Electrical power systems -- Thermal control of spacecraft -- Telecommunications -- Telemetry, command, data handling and processing -- Ground segment -- Spacecraft mechanisms -- Spacecraft electromagnetic compatibility engineering -- Assembly, integration and verification -- Small satellite engineering and application -- Product assurance -- Spacecraft system engineering.
Includes bibliographical references and index.
Hardcover
Keywords: Space vehicles -- Design and construction; Astronautics -- Systems engineering; TECHNOLOGY & ENGINEERING / Aeronautics & Astronautics